Production cross Sections of 109gIn,111gIn,113mIn and 115gCd Formed by Deuterons on Cadmium - Herreros Usher, O.; Wasilevsky, C.; De la Vega Vedoya, M.; Nassiff, S. J. (Akademische Verlagsgesellschaft, Wiesbaden, 1977)
Fil: Herreros Usher, O. Comisión Nacional de Energía Atómica; Argentina